ACVR1-activating mutation causes neuropathic pain and sensory neuron hyperexcitability in humans. Issue 1 (20th January 2023) - Yu, Xiaobing; Ton, Amy N.; Niu, Zejun; Morales, Blanca M.; Chen, Jiadong; Braz, Joao; Lai, Michael H.; Barruet, Emilie; Liu, Hongju; Cheung, Kin; Ali, Syed; Chan, Tea; et al.
Abstract : Supplemental Digital Content is Available in the Text. An ACVR1 activating mutation causes heat and mechanical pain hypersensitivity and induces sensory neuron hyperexcitability in humans. Abstract: Altered bone morphogenetic protein (BMP) signaling is associated with many musculoskeletal diseases. However, it remains unknown whether BMP dysfunction has direct contribution to debilitating pain reported in many of these disorders. Here, we identified a novel neuropathic pain phenotype in patients with fibrodysplasia ossificans progressiva (FOP), a rare autosomal-dominant musculoskeletal disorder characterized by progressive heterotopic ossification. Ninety-seven percent of these patients carry an R206H gain-of-function point mutation in the BMP type I receptor ACVR1 (ACVR1 R206H ), which causes neofunction to Activin A and constitutively activates signaling through phosphorylated SMAD1/5/8. Although patients with FOP can harbor pathological lesions in the peripheral and central nervous system, their etiology and clinical impact are unclear. Quantitative sensory testing of patients with FOP revealed significant heat and mechanical pain hypersensitivity. Although there was no major effect of ACVR1 R206H on differentiation and maturation of nociceptive sensory neurons (iSNs) derived from FOP induced pluripotent stem cells, both intracellular and extracellular electrophysiology analyses of the ACVR1 R206H iSNs displayed ACVR1-dependent hyperexcitability, a hallmark of neuropathic pain. Consistent with this phenotype, we recorded enhanced responses of ACVR1 R206H iSNs to TRPV1 and TRPA1 agonists. Thus, activated ACVR1 signaling can modulate pain processing in humans and may represent a potential target for pain management in FOP and related BMP pathway diseases.